Environmental Incidence of the Western Regiotram Project and its Contribution to the Objectives of Sustainable Development in Colombia - Martínez Rodríguez, Edgar Allan; Melgarejo Ruiz, Carlos Samuel; Riaño Serna, David Santiago; Rodriguez Gomez Valentina; Serrano Romero, Ronal Orlando; Monroy Vargas, Edgar Ricardo (Current Advances in Geography, Environment and Earth Sciences Vol. 7, 2022)
The Regiotram de Occidente It has been one of the largest innovations and development projects for the department of Cundinamarca in Colombia, since over the years and due to the great growth of the population in the area of influence of this sector of the country, transport of the inhabitants has caused great conflict, that is why this book chapter will demonstrate how the environmental impact assessment is related and its direct relationship with the sustainable development objectives (SDG) in the execution and construction of high impact for the environment in this sector of the country (Colombia), planting the relationship that this has with Latin American trains [1].